Issues of authorship threatening research integrity: Pointers for ethical publication practices - Albertyn, R. (South African Journal of Higher Education, 2025)
Publication imperatives have insidious consequences resulting in academic misconduct and “ghostly” authorship practices. If not exposed, these behaviours threaten research integrity and credibility in higher education. This article explores the systemic forces spawning gaming practices regarding the incentives in the neoliberal era and the implications for science. An investigation of ethical publication practice information was conducted by analysing the author guidelines of the 163 journals where academics in the largest faculty at a research-intensive university published articles in 2022. Findings reveal the issues where guidelines are not consistently clear and information not easily accessible. Guidelines for ethical publication practices regarding journal guidelines for authors, collegial discussion, research integrity education, and author support could contribute to constructively navigating the pressures associated with ethical publication.